2017
DOI: 10.1371/journal.pone.0169489
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Costs for Treating Relapsing Multiple Sclerosis and the Risk of Progression: A Retrospective Italian Cohort Study from 2001 to 2015

Abstract: BackgroundDisease modifying treatments (DMTs) are the main responsible for direct medical costs in multiple sclerosis (MS). The current investigation aims at evaluating possible associations between healthcare costs for treating relapsing remitting MS (RRMS) and disease evolution.MethodsThe present cohort study retrospectively included 544 newly diagnosed RRMS patients, prospectively followed up for 10.1±3.3 years. Costs for DMT administration and management were calculated for each year of observation. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
4
17
0
2
Order By: Relevance
“…Following diagnosis, patients rapidly fall out of employment, with recent data indicating that after 5 years only 25% of people are still working. As a result, MS has an economic impact disproportionate to its prevalence related to the high cost of disease modifying therapies (DMTs), the direct and indirect costs of relapses and associated costs of benefits and personal care [3].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Following diagnosis, patients rapidly fall out of employment, with recent data indicating that after 5 years only 25% of people are still working. As a result, MS has an economic impact disproportionate to its prevalence related to the high cost of disease modifying therapies (DMTs), the direct and indirect costs of relapses and associated costs of benefits and personal care [3].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Healthcare costs in MS are driven by the use of disease modifying treatments (DMTs), which are prescribed based on the initial severity of MS and on its subsequent progression. 50 Moccia et al 50 found that patients who received more expensive DMTs, specifically indicated for a more aggressive disease progression, presented better long-term outcomes (such as lower risk of reaching milestones of short-and long-term disease progression) compared with patients with relatively milder symptoms who received lower-cost DMTs. This issue should be considered not only by physicians when assessing patients with MS to design the most suitable course of treatment, but also by policy makers when establishing eligibility criteria for DMTs.…”
Section: Discussionmentioning
confidence: 99%
“…This issue should be considered not only by physicians when assessing patients with MS to design the most suitable course of treatment, but also by policy makers when establishing eligibility criteria for DMTs. 50,51 These more expensive DMTs could have beneficial effects on the MS patients' ability to work, which could be evaluated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Установлено, что весомый вклад в развитие этого мультифакторного заболевания вносят генетическая предрасположенность и экологические причины [5,6]. Увеличение распространенности РС в последние годы, рост прямых и косвенных затрат на его лечение определяют необходимость поиска путей первичной профилактики и новых подходов к терапии этого заболевания [7,8].…”
unclassified
“…населения -Целинный (75,4), Мамонтовский (74,3), Новичихинский (60,9), Славгородский (60,7), и районы, в которых этот показатель менее 10 на 100 тыс. населения -Немецкий национальный район (9,8), Быстроистокский (8,1), Чарышский (7,4), Крутихинский (7,2), Бурлинский (6,7), Егорьевский (6,3), Советский (5,6), Хабарский (5,2).…”
unclassified